(Hyper)nuclei and anti-(hyper)nuclei production in Pb-Pb collisions in ALICE at LHC. (April 2015) - Colocci, Manuel
Abstract: The ALICE detector at the LHC is used to study Pb-Pb collisions at = 2.76 TeV. At this energy almost equal amounts of matter and anti-matter are produced in the central rapidity region. This in turn enables the production of (hyper)nuclei and anti- (hyper)nuclei, which are measured with nearly identical abundances. Thanks to its high quality tracking and particle identification capabilities, the ALICE detector allows the investigation of these rarely produced (anti-)matter states. Preliminary results on the production of light (anti-)nuclei and (anti-)hypernuclei, and a search for exotic bound states are discussed in this article.